Esculetin inhibits the proliferation of human lung cancer cells by targeting epithelial-to-mesenchymal transition of the cells - Li, Hua; Wang, Qi; Wang, Yunli; Xu, Ze; Han, Zhong (Cellular and Molecular Biology, 2019)
Lung cancer is characterized by high mortality and it is a serious threat to human health. At present, strategies used for treatment of lung cancer are not effective. Hence, there is need for new drugs that can effectively treat the metastatic stage of the cancer. The present study investigated the effect of esculetin on proliferation and epithelial-mesenchymal transition (EMT) of human lung cancer (A549) cells, and the underlying mechanism.Cell proliferation was assessed using MTT assay. Real-time quantitative polymerase chain reaction (qRT-PCR) and Western blotting were employed for the determination of changes in the expression levels of vimentin, Snail and E-cadherin mRNAs. Cell invasion and migration were determined using Transwell assay. The results showed that esculetin significantly and time- and dose-dependently inhibited the proliferation of A549 cells (p < 0.05). It also significantly and dose-dependently reduced their invasive ability (p < 0.05). The levels of expression of vimentin and Snail mRNAs were significantly and dose-dependently down-regulated in esculetin-treated A549 cells, when compared with the control cells (p < 0.05). Esculetin treatment significantly and dose-dependently upregulated the expression of E-cadherin mRNA (p < 0.05). These results demonstrate that esculetin effectively inhibits the proliferation of A549 cells, and regulates EMT of the cells via the down-regulation of vimentin and Snail, and up-regulation of E-cadherin expressions.